VARIASI STRUKTUR ANATOMI DAUN DARI BEBERAPA JENIS TUMBUHAN MONOKOTIL SEBAGAI RANCANGAN LKPD PADA PEMBELAJARAN BIOLOGI SMA - Deviana Deviana; Imam Mahadi; Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was conducted to determine the variation of the leafanatomical structure of several types of monocot plants in January- October 2020. Thisresearch was conducted in 2 stages, namely the first stage: analysis of variations in theanatomical structure of the leaves of several types of monocot plants and the secondstage of LKPD design: potential analysis. development of teaching materials for thestructure and function of plant tissue for class XI SMA. This study used the paraffinmethod for leaf anatomical preparations in the Laboratory of FMIPA Biology, RiauUniversity and observation of preparations at the Laboratory of Biology, Study ofBiology Education, FKIP Riau University. The results of the research on the anatomicalstructure of the leaves tasbih ( Canna indica L), jagung ( Zea mays L), kayu apu ( Pistiastratiotes L) and eceng gondok ( Eichornia crassipes (Mart) Solm) showed variations inleaf anatomical structure based on qualitative and quantitative characters. Based onanalysis of the potential of the research results can be used as a structural materialLKPD design and function of plant tissue at study biology class XI SMA.Key Words: Anatomical Structure, Leaves, Monocot Plants, LKPD